Behavior of Concrete Beam Encasing Castellated Steel Section with Different Shear Stud Interactions (Al-Mansour Journal, 2025)
This study\\'s objective is to investigate the behavior of concrete-encased castellated steel sections with varying pore sizes. There two different types of Shear Stud Interactions: Partial (P) and Full (F). When shear connectors with F are used, stud connections combine the concrete and steel components. Four Composite beams that are simply supported were tested in settings of two-point loading. By encasing concrete in castellated steel beams, four instances were produced. The maximum pressure support capability of the structures was evaluated. Castellated beams are among the many features that are assessed when two different kinds of contact occur. in keeping with the test\\'s findings. The F interaction that the sample experienced when utilizing caused the final load percentages to rise by around 6.4%. The percentages of mid-deflection and horizontal displacement are reduced as well by 10% and 6.7%, respectively, as compared to the same sample when P interaction is used. Furthermore, at complete interaction, the sample with the same aperture showed a larger final load.
Keywords: Shear stud,Horizontal displacement,Full Interactions,Partial Interactions,mid-deflection.